2009
DOI: 10.1111/j.1439-0523.2008.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to anthracnose (Colletotrichum capsici) at seedling and fruiting stages in chili pepper (Capsicum spp.)

Abstract: Inheritance of resistance to anthracnose at fruiting and seedling stages was studied in two F 2 populations from a cross between Capsicum annuum cv. ÔBangchangÕ and Capsicum chinense ÔPBC932Õ. The first F 2 was used to study anthracnose resistance at fruiting stage on mature green and ripe red fruit, and the second F 2 was used to study the resistance at both seedling and fruiting stages. Fruit inoculation was performed on detached fruit using a microinjector. Disease severity was assessed on a 0-9 scale at 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
43
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 10 publications
6
43
0
3
Order By: Relevance
“…Some Colletotrichum isolates were pathogenic to unripe fruit of resistant genotypes 'PBC932' (C. chinense), 'PBC80' and 'PBC81' (C. baccatum), but they were not pathogenic to red fruit of those genotypes, which suggests that different resistance genes are expressed at different stages of fruit maturity (Taylor et al, 2007). A similar result was observed by Mahasuk et al (2009a), who studied the inheritance of resistance to C. capsici at different stages of fruit ripening (unripe and ripe) from crosses between Capsicum annuum (susceptible) and Capsicum chinense (resistant). They verified the involvement of two different genes responsible for resistance in ripe and unripe fruit, suggesting that the change in fruit maturation may have triggered the expression of different genes at different stages.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Some Colletotrichum isolates were pathogenic to unripe fruit of resistant genotypes 'PBC932' (C. chinense), 'PBC80' and 'PBC81' (C. baccatum), but they were not pathogenic to red fruit of those genotypes, which suggests that different resistance genes are expressed at different stages of fruit maturity (Taylor et al, 2007). A similar result was observed by Mahasuk et al (2009a), who studied the inheritance of resistance to C. capsici at different stages of fruit ripening (unripe and ripe) from crosses between Capsicum annuum (susceptible) and Capsicum chinense (resistant). They verified the involvement of two different genes responsible for resistance in ripe and unripe fruit, suggesting that the change in fruit maturation may have triggered the expression of different genes at different stages.…”
supporting
confidence: 53%
“…Kanchana-Udomkan et al (2004) found that fruit size does not affect the development of the disease, and unripe fruit of C. chinense were more susceptible to anthracnose caused by C. gloeosporioides than ripe fruit. Pakdeevaraporn et al (2005) and Mahasuk et al (2009a) showed that different genes control resistance to anthracnose in unripe and ripe fruit, which is extremely significant for Capsicum breeding seeking resistance to anthracnose. Mongkolporn et al (2010) also observed different reactions caused by the stage of development of Capsicum spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several researchers have used these genotypes in Capsicum breeding programs for resistance to anthracnose. As examples, we may cite studies developed by Pakdeevaraporn et al (2005) and Mahasuk et al (2009a), who crossed PBC932 (C. chinense) with 'Bangchang' (C. annuum). These authors noted that resistance was controlled by one gene (co1) in green fruit, by another (co2) red fruit, and yet another (co3) in seedlings, when using a C. capsici isolate identified as '158ci'.…”
Section: Exp12 -Resistance Assessment To Anthracnosementioning
confidence: 99%
“…In Capsicum genus, resistance control depends on the plant organ under study, such as leaf or fruit (Mahasuk et al, 2009a). In the case of fruit, resistance may also vary with maturation stage, whether immature or mature (Silva et al, 2014;Sun et al, 2015;Suwor et al, 2015).…”
Section: Exp12 -Resistance Assessment To Anthracnosementioning
confidence: 99%